Monitoramento informacional: um estudo de caso de Campina Grande/PB - Santos, Jimmy Felipe Gomes (2020)
This work began in the graduation of Law, which the author, for his profession of State Police had the opportunity to work during his professional life. Use of information in a stricto sensu concept is considered one of the concerns of society today. Its incorrect use generates problematic situations in all spheres. The limited view of this problem, probably has its initial phase due to the wide reach of the existing systems. Adopting computational tools - conceived mainly by the exact sciences - it is possible to cross-check the data, analyze it and, later, interpret it so that public agents make decisions. It is possible to act with the use of knowledge systems - specialized software created with the aim of identifying, correlating and suggesting solutions to help decision making by public managers when formulating public policies. The objective of this research is to investigate how Informational Monitoring is being used and can assist in the production of knowledge for decision making, with particular reference to the prevention, control and fight against crime. We opted for the field study, through the observation and data collection procedure. A priori, it is clear that new techniques adopted in specific sectors tend to have a form slowly incorporated into public management as a whole. Most of the time, other sectors take the lead and use methods and techniques with impressive advances in technologies in the most significant areas worldwide: communication and transport. Thus, they remain at the forefront of governments. As objects of study in this work, we have O Maior São João do Mundo, held during 2019 in the city of Campina Grande - PB, and the Bot para informações do COVID-19, created as a by-product of the information monitoring applied in O Maior São João do Mundo.